ANALISIS PEMBEBANAN LALU LINTAS PADAPERENCANAAN JALAN-JALAN PERINTIS - I Wayan Suweda (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2018)
Nusa Penida (20,284 ha) is nearly 2x the areas of the other three districts of Klungkung regency,which located in the Bali mainland (11,216 ha). However, the condition of people is very underdeveloped. The regionsdisparityis caused by various factor, one of them is